O livro didático de geografia no Ensino Médio: tensões e possibilidades para a educação do campo na região metropolitana de Belo Horizonte - Bruno Cesar de Resende (2015)
The textbook is one of the most used tools for the development of teaching-learning processes in the classroom. For this reason, the search for understanding of their structure and dynamics linked to its content and its production / circulation is an important field to be analyzed in light of the reflections it can bring to the pedagogical practice. The aim of this study was the analysis and observation of topics related to the field present in geography textbooks used in high schools located in rural areas of the Região Metropolitana de Belo Horizonte (RMBH) and the possibilities that these books can bring to the construction of Field Education. The research was built in two stages, one connected to geography teachers working in selected schools and another linked to the textbook selected by these schools. Part of the research with teachers was built by questionnaires and semi-structured interviews. Regarding books, the research was based on the analysis of its contents as well as the processes which are directly linked to production, such as the official ratings, publishing, the Programa Nacional do Livro Didático (PNLD) and the possible consequences of the historical evolution of this material in Brazil. Based on the analyzes and observations of the teaching relationship with the textbook and the production of this material a few points can be highlighted. Regarding the textbook: 1 - Its content still reverberates elements of theoretical and quantitative geographic school; 2 - That same content also brings elements derived from MEC / USAID agreements, like economist / production-nature; 3 - The two analyzed collections have significant differences in their theoretical and methodological aspects. Regarding teachers: 1 - not participated in the choice of textbooks they use. 2 - Do not have a teacher formated related to the reality of the field. 3 - Have working hours in two periods.